2022
DOI: 10.1021/acs.jnatprod.2c00240
|View full text |Cite
|
Sign up to set email alerts
|

Tolypocladamides A–G: Cytotoxic Peptaibols from Tolypocladium inflatum

Abstract: Seven new peptaibols named tolypocladamides A− G have been isolated from an extract of the fungus Tolypocladium inflatum, which inhibits the interaction between Raf and oncogenic Ras in a cell-based high-throughput screening assay. Each peptaibol contains 11 amino acid residues, an octanoyl or decanoyl fatty acid chain at the N-terminus, and a leucinol moiety at the C-terminus. The peptaibol sequences were elucidated on the basis of 2D NMR and mass spectral fragmentation analyses. Amino acid configurations wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…isolate (order Hypocreales, family Ophiocordycipitaceae): LP237-F5, LP237-F7, LP237-F8, 17,18 the dakwaabakains A−E, 16 and the tolypocladamides A−H. 19,20 This is the first report of an endophytic Tolypocladium sp. producing lipopeptaibols, and although they are structurally similar to the previously isolated Tolypocladium lipopeptaibols, the tolypocaibols are the first examples of this group to contain a C-terminal valinol instead of a leucenol.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…isolate (order Hypocreales, family Ophiocordycipitaceae): LP237-F5, LP237-F7, LP237-F8, 17,18 the dakwaabakains A−E, 16 and the tolypocladamides A−H. 19,20 This is the first report of an endophytic Tolypocladium sp. producing lipopeptaibols, and although they are structurally similar to the previously isolated Tolypocladium lipopeptaibols, the tolypocaibols are the first examples of this group to contain a C-terminal valinol instead of a leucenol.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…While the peptaibiotics encompass N -acylated linear peptides of between five and 22 amino acid residues with a high occurrence of Aib and other nonproteinogenic amino acids, the peptaibols are characterized by the additional presence of a C-terminal amino alcohol and represent the largest subclass of peptaibiotics. , Peptaibols that contain a lipophilic N -acyl moiety (typically octanoyl to pentadecenoyl chains) are further classified as lipopeptaibols, with 16 members of this class having been isolated from insect pathogens or soil/sediment-inhabiting fungal species congeneric with our Tolypocladium sp. isolate (order Hypocreales, family Ophiocordycipitaceae): LP237-F5, LP237-F7, LP237-F8, , the dakwaabakains A–E, and the tolypocladamides A–H. , This is the first report of an endophytic Tolypocladium sp. producing lipopeptaibols, and although they are structurally similar to the previously isolated Tolypocladium lipopeptaibols, the tolypocaibols are the first examples of this group to contain a C-terminal valinol instead of a leucenol.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Peptaibols are linear peptides typically with 5–21 amino acid residues that are characterized by the presence of nonproteinogenic amino acids, an acylated N-terminus, and a C-terminus that has been reduced to a 2-amino alcohol. , Very lipophilic peptaibols with a long-chain acyl group at the N-terminus are called lipopeptaibols. Peptaibols are known to be produced by several genera of soil-borne and plant pathogenic fungi, especially Trichoderma , but also Acremonium , Chlonostachys , Emericellopsis , and Tolypocladium , among others. , Peptaibols are best known for their antibacterial properties; however some have also been shown to have other bioactivities including antifungal, neuroleptic, and cytotoxic activities . Studies have revealed that their mechanism of action is mostly connected with the creation of voltage-dependent ion channels in cell membranes …”
mentioning
confidence: 99%